Seroepidemiology and molecular diversity of Leishmania donovani complex in Georgia - Babuadze, Giorgi (Parasit Vectors, 2016)
BACKGROUND: Leishmaniasis includes multiple clinical syndromes, most notably visceral, cutaneous, and mucosal forms. Visceral leishmaniasis (VL), also known as kala-azar, is a potentially fatal disease endemic to large parts of Africa and Asia, and in South-Eastern Europe (Greece, Turkey, Georgia). Visceral leishmaniasis is a parasitic zoonosis caused by species of the L. donovani complex. In the classical epidemiological model the main reservoir for VL are canines. METHODS: The study included a cohort of 513 individuals of both genders (190 males and 323 females) from the ages of 1 to 70 years that were screened in ten villages across two districts in Kakheti using the Kalazar Detect™ rK39 rapid diagnostic test. The phylogenetic diversity patterns of local strains, based on the rDNA internal transcribed spacer (ITS) sequences, were assessed for samples obtained from patients with suspected L. donovani infection, from canine reservoirs and from Phlebotomus sand flies obtained from different geographical areas of Georgia and from Azerbaijan. RESULTS: Out of a total of 600 domestic dog blood samples 95 (15.8 %) were positive by rK39 rapid diagnostic tests. For symptomatic domestic dogs, the testing of conjunctival swabs or bone marrow aspirates revealed a higher VL incidence in Kvareli District (Kvareli; 19.4 %, n = 329) compared with that observed for Sagarejo District (Sagarejo; 11.4 %, n = 271). A total of 231 sand flies of both genders were collected during the 2-month period; of the 114 females, 1.75 % were PCR positive for the presence of Leishmania spp. CONCLUSIONS: VL infection rates remain high in both canines and humans in Georgia, with disease in several known natural foci. The genetic relationships derived from rDNA internal transcribed spacer (ITS) sequence comparisons identified genetic subgroups, revealing preliminary insights into the genetic structure of L. donovani complex members currently circulating in the South Caucasus and demonstrates the utility of ITS-based genotyping in the resource-limited country of Georgia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1558-6) contains supplementary material, which is available to authorized users.